Investigating Hybrid Learning Strategies: Does it Affect Creativity? - Aminah Zb; M. Eval Setiawan; Edi Rozal; Fauzan Sulman (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to investigate the ability of the Hybrid Learning learning model on the creativity of biology education students in the educational innovation course. This research has been carried out using a quantitative approach with a quasi-experimental pretest-posttest control group design. The population in this study were biology education students in semester VI, Faculty of Education and Teacher Training at Sulthan Thaha Saifuddin State Islamic University Jambi, namely four classes with a population of 37 people, which was then sampled using the purposive sampling method where class VIA and VIC were the Experiment Class and Class VIB and VID was as a Control Class. The instrument used is was a test in the form of a description of ten items regarding creativity. Data analysis in this study used t-tes. The results of the investigation showed a significant influence on the creativity of students who used hybrid learning even though lectures were conducted remotely and in the midst of the Covid-19 pandemic.